Lithium secondary battery

The integration of a Co-Mg intermediate layer between the positive electrode and separator in lithium secondary batteries addresses the issue of interface destruction, ensuring high durability and effective discharge capacity retention during high-speed charging and discharging.

JP7612835B2Active Publication Date: 2025-01-14NGK INSULATORS LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023510240
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-03-30
Filing Date
2021-12-17
Publication Date
2025-01-14
Estimated Expiration
2041-12-17

AI Technical Summary

Technical Problem

Lithium secondary batteries experience deterioration in charging and discharging characteristics, especially when used at high speeds, due to destruction of the interface between the positive electrode and the separator, leading to a decrease in discharge capacity.

Method used

Incorporating an intermediate layer containing cobalt (Co) and magnesium (Mg) between the positive electrode layer made of lithium cobalt oxide and the separator made of magnesia, which suppresses interface destruction and maintains discharge capacity even with repeated high-speed charging and discharging.

Benefits of technology

The intermediate layer enhances the durability of the lithium secondary battery, maintaining discharge capacity and improving cycle characteristics by preventing interfacial destruction and facilitating efficient lithium ion movement.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007612835000002
    Figure 0007612835000002
  • Figure 0007612835000003
    Figure 0007612835000003
  • Figure 0007612835000004
    Figure 0007612835000004
Patent Text Reader

Abstract

The present invention addresses the problem of providing a lithium secondary battery which has excellent durability and in which discharge capacity is maintained even when charging and discharging are repeated at high speed. The lithium secondary battery comprises: a positive electrode composed of a sintered body containing a lithium cobalt oxide; a negative electrode; and a separator composed of a magnesia-containing sintered body interposed between the positive electrode and the negative electrode, the lithium secondary battery further comprising, between the positive electrode and the separator, an intermediate layer including an oxide containing Co and Mg.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a lithium secondary battery. This application claims priority based on Japanese Patent Application No. 2021-58569 filed on March 30, 2021, and incorporates by reference all of the contents of said Japanese Patent Application. [Background technology]

[0002] Lithium secondary batteries are known that include a positive electrode layer made of a sintered body of lithium composite oxide, a negative electrode layer made of a titanium-containing sintered body, and a ceramic separator interposed between the positive electrode layer and the negative electrode layer. For example, Patent Document 1 discloses a lithium secondary battery that is made of an integrated sintered plate in which a positive electrode layer, a ceramic separator, and a negative electrode layer are bonded together and that is impregnated with an electrolyte. In the lithium secondary battery disclosed in Patent Document 1, the ceramic separator is made of MgO and glass. In addition, the glass particles contained in the ceramic separator have a specific orientation at the interface between the negative electrode layer and the separator.

[0003] Patent Document 2 discloses a lithium secondary battery that is composed of an integral sintered plate in which a positive electrode layer, a ceramic separator, and a negative electrode layer are bonded together and that is impregnated with an electrolyte. In the lithium secondary battery disclosed in Patent Document 2, the titanium-containing sintered body that constitutes the negative electrode layer has a specific composition. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2019 / 221144 [Patent Document 2] Patent No. 6643528 Summary of the Invention [Problem to be solved by the invention]

[0005] With the development of devices using lithium secondary batteries, there is a demand for highly durable lithium secondary batteries that maintain their discharge capacity even when repeatedly charged and discharged at high rates.

[0006] Therefore, one of the objects of the invention according to the present disclosure is to provide a lithium secondary battery that has excellent durability and maintains its discharge capacity even when it is repeatedly charged and discharged at high speed. [Means for solving the problem]

[0007] The lithium secondary battery according to the present disclosure includes a positive electrode made of a sintered body containing lithium cobalt oxide, a negative electrode, and a separator made of a sintered body containing magnesia and disposed between the positive electrode and the negative electrode. The lithium secondary battery further includes an intermediate layer between the positive electrode and the separator, the intermediate layer including an oxide containing Co and Mg. Effect of the Invention

[0008] According to the above-mentioned lithium secondary battery, it is possible to provide a lithium secondary battery having excellent durability, in which the discharge capacity is maintained even when charging and discharging are repeated at high speed. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a schematic cross-sectional view showing the structure of a lithium secondary battery according to the present disclosure. [Diagram 2] FIG. 2 is a SEM image of a positive electrode, separator, and intermediate layer of a lithium secondary battery according to the present disclosure. [Diagram 3] FIG. 3 is a graph showing the results of EDS analysis at each of the marking points 4 to 7 shown in FIG. [Figure 4] FIG. 4 is a SEM image of a positive electrode, separator, and intermediate layer of a lithium secondary battery according to the present disclosure. [Diagram 5] FIG. 5 is a black and white binarized image of the intermediate layer portion in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] [Overview of the embodiment] First, the embodiments of the present disclosure will be described. The lithium secondary battery of the present disclosure includes a positive electrode made of a sintered body containing lithium cobalt oxide, a negative electrode, and a separator made of a sintered body containing magnesia and interposed between the positive electrode and the negative electrode. The lithium secondary battery further includes an intermediate layer containing an oxide containing Co and Mg between the positive electrode and the separator.

[0011] Conventionally, it is known that in lithium secondary batteries, the charge / discharge characteristics deteriorate with repeated charging and discharging. It is also known that this phenomenon becomes more pronounced when charging and discharging are repeated at a high rate. Therefore, the inventors have conducted extensive research in order to provide a lithium secondary battery with excellent durability that maintains its discharge capacity even when charging and discharging are repeated at a high rate. The inventors have conducted research focusing on an integrally sintered plate type lithium secondary battery in which a positive electrode layer, a ceramic separator, and a negative electrode layer are bonded to each other. Then, they found that in a sintered body in which a positive electrode containing a lithium composite oxide and a separator containing magnesia are integrally sintered, when repeated charging and discharging are performed over a long period of time, interfacial destruction may occur at the bonding interface between the positive electrode and the separator.

[0012] If the interface between the positive electrode and the separator is destroyed, the opposing positions of the positive electrode, separator, and negative electrode may shift. If the opposing positions shift, direct electron transfer occurs between the positive electrode and the negative electrode, and a small short-circuit current may flow. A short circuit between the positive electrode and the negative electrode causes a significant loss of discharge capacity.

[0013] The inventors have found that one of the reasons for the destruction at the interface between the positive electrode and the separator is that the volume of the positive electrode changes during charging and discharging, while the volume of the separator does not change. As a result of their investigation, they have found that the deterioration of the charge-discharge characteristics can be suppressed by providing an intermediate layer having a specific composition between the positive electrode layer containing lithium cobalt oxide and the separator containing magnesia.

[0014] Without being bound by any particular theory, it is believed that the lithium secondary battery disclosed herein includes an intermediate layer containing an oxide containing cobalt (Co) and magnesium (Mg) between a positive electrode layer containing lithium cobalt oxide and a separator containing magnesia, thereby suppressing the destruction of the interface between the positive electrode and the separator. It is believed that this suppresses the decrease in discharge capacity when charging and discharging at high speed is repeated, and a lithium secondary battery with excellent durability that maintains the discharge capacity even when charging and discharging at high speed is obtained.

[0015] In the lithium secondary battery, the separator may be a plate-like separator including a first main surface and a second main surface located on the opposite side of the first main surface in the thickness direction, and the positive electrode, the intermediate layer, and the separator may be integrally formed into a sintered plate. By adopting such a configuration, the integrity of the positive electrode and the separator can be improved, and a lithium secondary battery that is small and has a high energy density can be provided.

[0016] In the lithium secondary battery, the thickness of the intermediate layer may be 1 μm or more and 50 μm or less. When the thickness of the intermediate layer is in this range, a lithium secondary battery having particularly good cycle characteristics can be obtained. In other words, the effect of suppressing deterioration of discharge performance when repeatedly charging and discharging is large. When the thickness of the intermediate layer is 1 μm or more, the effect of the presence of the intermediate layer becomes more clear. In addition, when the thickness of the intermediate layer is 50 μm or less, it is considered that the degree to which the diffusion of lithium ions is hindered by the intermediate layer is sufficiently low, and the cycle characteristics can be improved.

[0017] In the lithium secondary battery, the porosity of the intermediate layer may be 15% or more and 50% or less. When the porosity of the intermediate layer is within this range, the pores can be easily filled with an electrolyte without gaps. This allows the intermediate layer to not significantly impede the movement of Li between the positive and negative electrodes during charging and discharging, making it possible to charge and discharge at a higher speed.

[0018] In the lithium secondary battery, the average particle diameter of the intermediate layer may be 1 μm or more and 10 μm or less. Here, the average particle diameter is the average length of the continuous oxide particles that constitute the intermediate layer. Since the intermediate layer is formed by an aggregation of particles and the average particle diameter of the particles is within this numerical range, the sintering strength between the particles is improved, cohesive failure is less likely to occur in the intermediate layer, and the effect of maintaining the charge / discharge characteristics is further improved.

[0019] In the lithium secondary battery, the ratio Mg / Co of the amount of elements Mg and Co present in the intermediate layer may decrease from the side in contact with the separator toward the side in contact with the positive electrode. By making the intermediate layer have a relatively high Mg content on the side closer to the separator containing magnesia and a relatively high Co content on the side closer to the positive electrode containing cobalt, the continuity between the intermediate layer and the separator and between the intermediate layer and the positive electrode are further improved. As a result, the interface is less likely to break, and the effect of maintaining the charge / discharge characteristics is further improved.

[0020] In the lithium secondary battery, the intermediate layer may have a first portion and a second portion, and the porosity of the first portion may be different from that of the second portion. In other words, the intermediate layer may have a first portion and a second portion with different porosity. By having the portions with different porosity, the propagation of strain caused by the expansion and contraction of the positive electrode layer can be further suppressed, the continuity between the intermediate layer and the separator, and between the intermediate layer and the positive electrode is further improved, interfacial destruction is less likely to occur, and the effect of maintaining the charge and discharge characteristics is further improved.

[0021] [Specific Example of the Embodiment] Next, specific embodiments of the lithium secondary battery of the present disclosure will be described with reference to the drawings. In the following drawings, the same or corresponding parts are designated by the same reference characters and their description will not be repeated.

[0022] (Embodiment 1) (lithium secondary battery) FIG. 1 is a schematic cross-sectional view showing the structure of a lithium secondary battery according to one embodiment of the present disclosure. Referring to FIG. 1, a lithium secondary battery 10 includes a positive electrode layer 12, a negative electrode layer 16, a separator 20, an intermediate layer 15, an electrolyte 22, and an exterior body 24. The positive electrode layer 12 is made of a sintered body containing lithium cobalt oxide. The negative electrode layer 16 is made of a sintered body containing titanium, for example. The separator 20 is made of ceramic and is interposed between the positive electrode layer 12 and the negative electrode layer 16. The intermediate layer 15 is present between the positive electrode layer 12 and the separator 20. The electrolyte 22 is impregnated into the positive electrode layer 12, the negative electrode layer 16, the intermediate layer 15, and the separator 20.

[0023] The exterior body 24 has a sealed space, and the positive electrode layer 12, the intermediate layer 15, the negative electrode layer 16, the separator 20, and the electrolyte 22 are accommodated in this sealed space. The positive electrode layer 12, the intermediate layer 15, the separator 20, and the negative electrode layer 16 form one integral sintered body plate as a whole. That is, the positive electrode layer 12, the intermediate layer 15, the separator 20, and the negative electrode layer 16 are bonded to each other. In this specification, "forming one integral sintered plate" means that the four layers of the positive electrode layer 12, the intermediate layer 15, the separator 20, and the negative electrode layer 16 are connected and bonded to each other without relying on other bonding methods such as adhesives. In addition, the positive electrode layer 12, the intermediate layer 15, and the separator 20 form an integral sintered plate, and the negative electrode layer 16 may be a sintered body formed separately from the integral sintered plate.

[0024] The exterior body 24 may be appropriately selected depending on the type of the lithium secondary battery 10. For example, when the lithium secondary battery is in the form of a coin-shaped battery as shown in FIG. 1, the exterior body 24 typically includes a positive electrode can 24a, a negative electrode can 24b, and a gasket 24c, and the positive electrode can 24a and the negative electrode can 24b are crimped via the gasket 24c to form a sealed space. The positive electrode can 24a and the negative electrode can 24b may be made of a metal such as stainless steel, and are not particularly limited. The gasket 24c may be an annular member made of an insulating resin such as polypropylene, polytetrafluoroethylene, or PFA resin, and are not particularly limited.

[0025] Although the lithium secondary battery 10 shown in FIG. 1 is in the form of a coin-type battery, the form of the lithium secondary battery according to the present disclosure is not limited thereto. For example, it may be in other forms such as a thin secondary battery including a chip-type secondary battery and a pouch-type secondary battery. When the lithium secondary battery is a chip battery that can be built into a card, the exterior body is preferably a resin substrate, and the battery elements (i.e., the positive electrode layer 12, the negative electrode layer 16, the ceramic separator 20, and the electrolyte 22) are preferably embedded in the resin substrate. For example, when the lithium secondary battery is a pouch-type secondary battery, the battery elements may be sandwiched between a pair of resin films. The pair of resin films may be bonded together with an adhesive. In addition, the pair of resin films may be heat-sealed to each other by a hot press.

[0026] Referring to FIG. 1, the lithium secondary battery 10 includes a positive electrode collector 14 and a negative electrode collector 18. The positive electrode collector 14 and the negative electrode collector 18 are not particularly limited, but are preferably metal foils such as copper foil and aluminum foil. The positive electrode collector 14 is preferably disposed between the positive electrode layer 12 and the outer casing 24 (e.g., a positive electrode can 24a). The negative electrode collector 18 is preferably disposed between the negative electrode layer 16 and the outer casing 24 (e.g., a negative electrode can 24b). In addition, a positive electrode-side carbon layer 13 is preferably provided between the positive electrode layer 12 and the positive electrode collector 14 from the viewpoint of reducing contact resistance. Similarly, a negative electrode-side carbon layer 17 is preferably provided between the negative electrode layer 16 and the negative electrode collector 18 from the viewpoint of reducing contact resistance. Both the positive electrode-side carbon layer 13 and the negative electrode-side carbon layer 17 are preferably made of conductive carbon, and may be formed, for example, by applying a conductive carbon paste by screen printing or the like.

[0027] (Positive electrode layer) The positive electrode layer 12 is composed of a plate-shaped sintered body containing lithium cobaltate. The positive electrode layer 12 can be made to contain no binder or conductive assistant. As the lithium cobaltate, specifically, for example, LiCoO2 (hereinafter sometimes abbreviated as LCO) can be mentioned. As the LCO sintered body formed in a plate shape, for example, those disclosed in Japanese Patent No. 5587052 and International Publication No. 2017 / 146088 can be used. The positive electrode layer 12 preferably contains a plurality of primary particles composed of lithium cobaltate, and the plurality of primary particles are oriented at an average orientation angle of more than 0° and 30° or less with respect to the layer plane of the positive electrode layer, and is an oriented positive electrode layer. Examples of the structure, composition, and identification method of such an oriented positive electrode layer include those disclosed in Patent Document 1 (International Publication No. 2019 / 221144).

[0028] As the lithium cobaltate constituting the primary particles, in addition to LCO, for example, Li x NiCoO2 (lithium nickel cobaltate), Li x CoNiMnO2 (lithium cobalt nickel manganate), Li x CoMnO2 (lithium cobalt manganate), etc. can be mentioned. Further, in addition to lithium cobaltate, other lithium composite oxides may be included. Examples of the lithium composite oxide include Li x MO2 (where 0.05 < x < 1.10, M is at least one kind of transition metal, and M typically includes one or more of Co, Ni, and Mn), and oxides represented thereby can be mentioned.

[0029] The average particle size of the plurality of primary particles constituting the positive electrode layer 12 is preferably 5 μm or more. Specifically, the average particle size of the primary particles used for calculating the average orientation angle is preferably 5 μm or more, more preferably 7 μm or more, and still more preferably 12 μm or more.

[0030] The positive electrode layer 12 may contain pores. When the sintered body contains pores, particularly open pores, an electrolyte can be allowed to penetrate into the sintered body when the sintered body is incorporated into a battery as a positive electrode layer, and as a result, lithium ion conductivity can be improved. The porosity of the positive electrode layer 12 is preferably 20 to 60%, more preferably 25 to 55%, further preferably 30 to 50%, and particularly preferably 30 to 45%. The porosity of the sintered body can be measured by the method described in the Examples below.

[0031] The average pore size of the positive electrode layer 12 is preferably 0.1 to 10.0 μm, more preferably 0.2 to 5.0 μm, and further preferably 0.25 to 3.0 μm. Within the above range, local stress concentration in large pores is suppressed, and stress in the sintered body is easily released uniformly. In addition, improvement of lithium ion conductivity due to internal penetration of the electrolyte through the pores can be more effectively achieved.

[0032] The thickness of the positive electrode layer 12 is preferably 60 to 600 μm, more preferably 60 to 500 μm, and further preferably 70 to 400 μm. Within such a range, the active material capacity per unit area is increased to improve the energy density of the lithium secondary battery 10, and deterioration of the battery characteristics (particularly an increase in the resistance value) due to repeated charging and discharging can be suppressed.

[0033] (Separator) The separator 20 is a plate-shaped separator including a first main surface and a second main surface located on the opposite side to the first main surface in the thickness direction. The negative electrode layer 16 is disposed in contact with the first main surface of the separator 20. The intermediate layer 15 is disposed on the second main surface side of the separator 20, and the separator 20 and the intermediate layer 15 are sintered together and are continuous. The separator 20 is a ceramic microporous film. The separator 20 has excellent heat resistance and can be manufactured as a single integrated sintered plate together with the positive electrode layer 12 and the intermediate layer 15. The integrated sintered plate may further include the negative electrode layer 16.

[0034] The separator 20 includes magnesia (MgO). Specifically, for example, the separator 20 may be composed of magnesia (MgO) and glass. In the separator 20, the MgO and glass are present in the form of particles bonded to each other by sintering. The ceramics included in the separator 20 may include Al2O3, ZrO2, SiC, Si3N4, AlN, etc., in addition to MgO and glass.

[0035] The glass contained in the separator 20 preferably contains 25% by weight or more of SiO2, more preferably 30 to 95% by weight, even more preferably 40 to 90% by weight, and particularly preferably 50 to 80% by weight. The glass content in the separator 20 is preferably 3 to 70% by weight, more preferably 5 to 50% by weight, even more preferably 10 to 40% by weight, and particularly preferably 15 to 30% by weight, based on the total weight of the separator 20. When the content is within this range, both a high yield and excellent charge / discharge cycle characteristics can be effectively achieved. The addition of the glass component to the separator 20 is preferably performed by adding glass frit to the raw material powder of the separator. The glass frit preferably contains one or more of Al2O3, B2O3, and BaO as a component other than SiO2.

[0036] The thickness of the separator 20 is preferably 5 to 50 μm, more preferably 5 to 40 μm, further preferably 5 to 35 μm, and particularly preferably 8 to 30 μm. The porosity of the separator 20 is preferably 30 to 85%, and more preferably 40 to 80%.

[0037] (Middle class) The intermediate layer 15 is a layer formed between the positive electrode layer 12 and the separator 20. The positive electrode layer 12 is sintered integrally with the first main surface of the intermediate layer 15, and the separator 20 is sintered integrally with the second main surface of the intermediate layer 15. The intermediate layer 15 can be distinguished from the positive electrode layer 12 and the separator 20 present on both sides thereof mainly by the difference in composition. A method for identifying the position of the intermediate layer 15 in the composite of the positive electrode layer 12, the intermediate layer 15, and the separator 20 sintered integrally will be described in detail in the Examples.

[0038] The intermediate layer 15 includes an oxide containing cobalt (Co) and magnesium (Mg). An example of the oxide containing cobalt and magnesium is a composition in which LCO and MgO are mixed in a ratio of 3:1 to 5:1. The oxide containing cobalt is not limited to LCO, and examples thereof include CoO, Co3O4, Co2O3, CoFe2O4, CoMoO4, CoTiO3, and CoWO4. The oxide containing Mg is not limited to MgO, and examples thereof include MgAl2O4, MgFe2O4, MgMoO4, MgTiO3, MgWO4, and MgSiO3. The oxide containing cobalt and magnesium is an oxide in which cobalt and magnesium exist in a solid solution state (Co x ,Mg y )O (wherein x+y=1) or (Co x ,Mg y )3O4 (wherein x+y=1). Also, mixtures of these oxides are possible.

[0039] The thickness of the intermediate layer 15 is not particularly limited, but is preferably 0.5 to 70 μm, and more preferably 1 to 50 μm. It is believed that if the thickness of the intermediate layer 15 is 1 μm or more, the effect of preventing the interface destruction between the positive electrode 12 and the separator 20 can be obtained even when charging and discharging are repeated. In addition, if the thickness of the intermediate layer 15 is 50 μm or less, the distance between the positive electrode 12 and the negative electrode 16 is not too large, and the degree of inhibition of the diffusion of lithium ions during charging and discharging is sufficiently low, and it is believed that the cycle characteristics can be improved.

[0040] The intermediate layer 15 has a structure in which a plurality of (i.e., a large number of) primary particles are bonded together. These primary particles are preferably composed of an oxide containing cobalt (Co) and magnesium (Mg). The primary particle size, which is the average particle size of the plurality of primary particles constituting the intermediate layer 15, is preferably 20 μm or less, more preferably 0.5 to 15 μm, and even more preferably 1 to 10 μm. When within these ranges, the sintering strength between the particles is improved, cohesive failure is less likely to occur in the intermediate layer, and the effect of maintaining the charge / discharge characteristics is further improved. The average particle size is the average value of the length over which the oxide constituting the intermediate layer exists in succession, and a specific measurement method is described in detail in the Examples.

[0041] The intermediate layer 15 preferably contains pores. When the sintered body contains pores, particularly open pores, and is incorporated into a battery together with the positive electrode layer 12, the electrolyte can penetrate into the sintered body, thereby improving the lithium ion conductivity. The porosity of the intermediate layer 15 is preferably 5 to 60%, more preferably 10 to 55%, and further preferably 15 to 50%. The average pore size of the intermediate layer 15 may be 0.05 to 20 μm, preferably 0.1 to 15 μm, and more preferably 0.15 to 10 μm.

[0042] The intermediate layer 15 may have a uniform composition throughout its thickness, or the composition may vary in the thickness direction. Specifically, for example, the ratio of the element amounts of Mg and Co (e.g., Mg / Co) may vary in the thickness direction of the intermediate layer. Specifically, for example, in the intermediate layer 15, it is preferable that Mg / Co decreases from the side in contact with the separator 20 toward the side in contact with the positive electrode 12. In other words, it is preferable that the Mg content ratio is higher on the side of the intermediate layer 15 closer to the separator 20 than on the side closer to the positive electrode 12. A method for measuring the content ratio of elements in the intermediate layer 15 will be described in detail in the Examples.

[0043] The intermediate layer 15 may be composed of a single part, or may be composed of two or more parts. Specifically, it may include two parts, which are the first part and the second part, or it may include three parts, which are the first part, the second part, and the third part. When it includes two or more parts, each part may have a different composition, physical property, and / or structure. For example, the first part and the second part in the intermediate layer 15 may have different porosities. In other words, the intermediate layer 15 may include two or more parts with different porosities. For example, the porosity of the first part may be 5 to 20%, and the porosity of the second part may be 20 to 60%. In this case, it is preferable that the first part is provided near the interface in contact with the separator 20 or near the interface in contact with the positive electrode layer 12, and the second part is provided inside not in contact with the separator 20 or the positive electrode layer 12. Also, for example, the intermediate layer 15 can be made up of three parts, a first part, a second part, and a third part. In this case, it is preferable that the porosity of the first part close to the positive electrode 12 and the third part close to the separator 20 is relatively low, and the porosity of the second part located in between is relatively high. With such a configuration, the propagation of strain due to the expansion and contraction of the positive electrode layer 12 can be further suppressed, the continuity between the intermediate layer 15 and the separator 20, and between the intermediate layer 20 and the positive electrode layer 12 is further improved, interfacial destruction is less likely to occur, and the effect of maintaining the charge and discharge characteristics is further improved.

[0044] The intermediate 15 that is fired integrally with the positive electrode layer 12 and the separator 20 can be obtained, for example, by sandwiching an intermediate layer green sheet between a positive electrode green sheet and a separator green sheet and firing them. In addition, the intermediate layer can be formed by setting specific firing conditions in firing the positive electrode green sheet and the separator green sheet. These methods will be described in detail in the Examples.

[0045] (Negative electrode layer) The negative electrode layer 16 is, for example, a plate-shaped sintered body containing a titanium-containing composition. The negative electrode layer 16 may be one that does not contain a binder or a conductive additive. The titanium-containing sintered body is lithium titanate Li4Ti5O 12It is preferable that the battery contains Li4Ti5O (hereinafter referred to as LTO) or niobium titanium composite oxide Nb2TiO7, and more preferably contains LTO. Although LTO is typically known to have a spinel structure, it can also adopt other structures during charging and discharging. For example, LTO is Li4Ti5O 12 (spinel structure) and Li7Ti5O 12 The reaction proceeds in the coexistence of two phases, i.e., LTO (rock salt structure). Therefore, LTO is not limited to a spinel structure. LTO may be partially substituted with other elements. Examples of other elements include Nb, Ta, W, Al, Mg, etc. The LTO sintered body can be manufactured, for example, according to the method described in JP 2015-185337 A.

[0046] The negative electrode layer 16 has a structure in which a plurality of (i.e., a large number of) primary particles are bonded together. These primary particles are preferably composed of LTO or Nb2TiO7. The negative electrode layer 16 may be configured as an integrated sintered body together with the positive electrode 12, the intermediate layer 15, and the separator 20. The negative electrode layer 16 may also be configured as a sintered body separate from the integrated sintered body of the positive electrode 12, the intermediate layer 15, and the separator 20, and combined in the lithium secondary battery 1.

[0047] The thickness of the negative electrode layer 16 is preferably 70 to 800 μm, more preferably 70 to 700 μm, even more preferably 85 to 600 μm, and particularly preferably 95 to 500 μm. The primary particle size, which is the average particle size of the multiple primary particles constituting the negative electrode layer 16, is preferably 1.2 μm or less, more preferably 0.02 to 1.2 μm, and even more preferably 0.05 to 0.7 μm.

[0048] The negative electrode layer 16 preferably contains pores. When the sintered body contains pores, particularly open pores, and is incorporated into a battery as a negative electrode layer, the electrolyte can penetrate into the sintered body, thereby improving the lithium ion conductivity. The porosity of the negative electrode layer 16 is preferably 20 to 60%, more preferably 30 to 55%, and even more preferably 35 to 50%. The average pore size of the negative electrode layer 16 is preferably 0.08 to 5.0 μm, more preferably 0.1 to 3.0 μm, and even more preferably 0.12 to 1.5 μm.

[0049] The negative electrode layer 16 is not limited to being made of a ceramic sintered body, and may be a so-called coated electrode. For example, the negative electrode layer 16 may be a carbon coating film containing a mixture of an active material such as LTO or graphite and a binder such as PVDF.

[0050] (electrolyte) The electrolyte 22 is not particularly limited, and any electrolyte known in the art for use in lithium secondary batteries may be used. For example, one or a combination of two or more selected from ethylene carbonate (EC), methyl ethyl carbonate (MEC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), propylene carbonate (PC), and γ-butyrolactone (GBL) may be used as the solvent. For example, lithium salt compounds such as lithium hexafluorophosphate (LiPF6) and lithium borofluoride (LiBF4) may be used as the electrolyte dissolved in the solvent. The electrolyte 22 may further contain at least one selected from vinylene carbonate (VC), fluoroethylene carbonate (FEC), vinyl ethylene carbonate (VEC), and lithium difluoro(oxalato)borate (LiDFOB) as an additive.

[0051] The concentration of the electrolyte in the electrolytic solution 22 is preferably 0.5 to 2 mol / L, more preferably 0.6 to 1.9 mol / L, further preferably 0.7 to 1.7 mol / L, and particularly preferably 0.8 to 1.5 mol / L.

[0052] As the electrolyte, a solid electrolyte or a polymer electrolyte can be used in addition to the electrolytic solution 22. In that case, it is preferable that the electrolyte is impregnated at least into the pores of the separator 20, as in the case of the electrolytic solution 22. The impregnation method is not particularly limited, but examples include a method of melting the electrolyte and infiltrating it into the pores of the separator 20, and a method of pressing a powder compact of the electrolyte against the separator 20.

[0053] [Example] The lithium secondary battery of the present disclosure will be described in more detail below with reference to examples and comparative examples. [Example 1] A lithium secondary battery was produced according to the following methods 1 to 3. The obtained lithium secondary battery was evaluated according to the methods 4 and 5.

[0054] 1. Preparation of separator-integrated positive electrode 1a. Preparation of LCO green sheet (positive electrode green sheet) First, Co3O4 powder (manufactured by Seido Chemical Industry Co., Ltd.) and Li2CO3 powder (manufactured by Honjo Chemical Co., Ltd.) were mixed so that the molar ratio of Li / Co was 1.01, and then the mixture was kept at 780°C for 5 hours. The obtained powder was pulverized in a pot mill so that the volumetric D50 was 0.4 μm, to obtain a powder consisting of LCO plate-like particles. 100 parts by weight of the obtained LCO powder, 100 parts by weight of a dispersion medium (toluene: isopropanol = 1:1), 10 parts by weight of a binder (polyvinyl butyral: product number BM-2, manufactured by Sekisui Chemical Co., Ltd.), 4 parts by weight of a plasticizer (DOP: Di (2-ethylhexyl) phthalate, manufactured by Kurogane Kasei Co., Ltd.), and 2 parts by weight of a dispersant (product name Rheodol SP-O30, manufactured by Kao Corporation) were mixed. The obtained mixture was stirred under reduced pressure to defoam it, and the viscosity was adjusted to 4000 cP to prepare an LCO slurry. The viscosity was measured using a Brookfield LVT viscometer. The slurry thus prepared was formed into a sheet on a PET film by a doctor blade method to form an LCO green sheet. The thickness of the LCO green sheet was adjusted to 200 μm after firing.

[0055] 1b. Preparation of MgO green sheet (separator green sheet) Magnesium carbonate powder (manufactured by Konoshima Chemical Co., Ltd.) was heat-treated at 900°C for 5 hours to obtain MgO powder. The obtained MgO powder and glass frit (manufactured by Nippon Frit Co., Ltd., CK0199) were mixed at a weight ratio of 4:1. 100 parts by weight of the obtained mixed powder (volume-based D50 particle size 0.4 μm), 100 parts by weight of a dispersion medium (toluene: isopropanol = 1:1), 20 parts by weight of a binder (polyvinyl butyral: product number BM-2, manufactured by Sekisui Chemical Co., Ltd.), 4 parts by weight of a plasticizer (DOP: Di (2-ethylhexyl) phthalate, manufactured by Kurogane Kasei Co., Ltd.), and 2 parts by weight of a dispersant (product name Rheodol SP-O30, manufactured by Kao Corporation) were mixed. The obtained raw material mixture was stirred under reduced pressure to defoam it, and the viscosity was adjusted to 4000 cP to prepare a slurry. The viscosity was measured with a Brookfield LVT type viscometer. The slurry thus prepared was formed into a sheet on a PET film by a doctor blade method to form an MgO green sheet, the thickness of which was adjusted to 10 μm after firing.

[0056] 1c. Preparation of LCO-MgO mixed green sheet (intermediate layer green sheet) First, Co3O4 powder (manufactured by Seido Chemical Industry Co., Ltd.) and Li2CO3 powder (manufactured by Honjo Chemical Co., Ltd.) were weighed so that the molar ratio of Li / Co was 1.01, and then mixed. The mixture was kept at 780°C for 5 hours, and the resulting powder was pulverized in a pot mill so that the volumetric D50 was 7 μm, to obtain a powder consisting of LCO plate-like particles. Next, magnesium carbonate powder (manufactured by Konoshima Chemical Co., Ltd.) was heat-treated at 900° C. for 5 hours to obtain MgO powder. The obtained LCO powder and MgO powder were mixed at a weight ratio of 4:1. 100 parts by weight of the obtained mixed powder, 100 parts by weight of a dispersion medium (toluene: isopropanol = 1:1), 20 parts by weight of a binder (polyvinyl butyral: product number BM-2, manufactured by Sekisui Chemical Co., Ltd.), 4 parts by weight of a plasticizer (DOP: Di (2-ethylhexyl) phthalate, manufactured by Kurogane Kasei Co., Ltd.), and 2 parts by weight of a dispersant (product name Rheodol SP-O30, manufactured by Kao Corporation) were mixed. The obtained raw material mixture was stirred under reduced pressure to degas and the viscosity was adjusted to 4000 cP to prepare a slurry. The viscosity was measured with an LVT type viscometer manufactured by Brookfield. The slurry thus prepared was formed into a sheet on a PET film by the doctor blade method to form an LCO-MgO mixed green sheet. The thickness of the LCO-MgO mixed green sheet was set so that the thickness after firing was 15 μm.

[0057] 1d. Preparation of separator-integrated positive electrode plate (lamination of green sheets, compression bonding and firing) The positive electrode green sheet, intermediate layer green sheet, and separator green sheet are stacked in this order, and the resulting laminate is subjected to CIP (cold isostatic pressing) at 200 kgf / cm 2 The green sheets were pressed together with a press. The laminate thus pressed was punched out into a disk shape with a diameter of 10 mm using a punching die. The obtained disk-shaped laminate was degreased at 600°C for 5 hours, and then heated to 800°C at a rate of 1000°C / h and held there for 10 minutes for firing, and then cooled. In this way, a separator-integrated positive electrode plate was obtained, which included three layers: a positive electrode layer (LCO sintered body layer), an intermediate layer, and a separator layer (MgO separator layer).

[0058] 1e. Bonding of positive electrode current collector with conductive carbon paste Acetylene black and polyamideimide were weighed out to a mass ratio of 3:1, and mixed with an appropriate amount of NMP (N-methyl-2-pyrrolidone) as a solvent to prepare a conductive carbon paste as a conductive adhesive. Next, the conductive carbon paste was screen-printed on an aluminum foil as a positive electrode collector. The separator-integrated positive electrode plate was placed so that the positive electrode surface was adhered within the undried printing pattern (i.e., the area coated with the conductive carbon paste), and vacuum dried at 60°C for 30 minutes to prepare a separator-integrated positive electrode in which the separator-integrated positive electrode plate and the positive electrode collector were adhered via a positive electrode-side carbon layer. The thickness of the positive electrode-side carbon layer was set to 10 μm.

[0059] 2. Preparation of the Negative Electrode 2a. Preparation of LTO green sheet (negative electrode green sheet) First, 100 parts by weight of LTO powder (volume standard D50 particle size 0.06 μm, manufactured by Sigma-Aldrich Japan LLC), 100 parts by weight of dispersion medium (toluene: isopropanol = 1:1), 20 parts by weight of binder (polyvinyl butyral: product number BM-2, manufactured by Sekisui Chemical Co., Ltd.), 4 parts by weight of plasticizer (DOP: Di (2-ethylhexyl) phthalate, manufactured by Kurogane Kasei Co., Ltd.), and 2 parts by weight of dispersant (product name Rheodol SP-O30, manufactured by Kao Corporation) were mixed. The obtained negative electrode raw material mixture was stirred and degassed under reduced pressure, and the viscosity was adjusted to 4000 cP to prepare an LTO slurry. The viscosity was measured with an LVT type viscometer manufactured by Brookfield. The slurry thus prepared was formed into a sheet shape on a PET film by the doctor blade method to form an LTO green sheet. The thickness of the LTO green sheet was set so that the thickness after firing was 275 μm.

[0060] 2b. Preparation of negative electrode plate (firing of LTO green sheet) The LTO green sheet was punched out into a disk shape with a diameter of 9.8 mm using a punching die. The obtained disk-shaped laminate was degreased at 600°C for 5 hours, then heated to 800°C at a rate of 1000°C / h and held there for 10 minutes, after which it was sintered and cooled. Thus, a negative electrode plate was obtained.

[0061] 2c. Bonding of negative electrode current collector with conductive carbon paste Acetylene black and polyamideimide were weighed out to a mass ratio of 3:1 and mixed with an appropriate amount of NMP (N-methyl-2-pyrrolidone) as a solvent to prepare a conductive carbon paste as a conductive adhesive. Next, the conductive carbon paste was screen-printed on an aluminum foil as a negative electrode current collector. A negative electrode plate was placed so that it was within the undried printing pattern (i.e., the area coated with the conductive carbon paste), and vacuum-dried at 60°C for 30 minutes to prepare a negative electrode in which the negative electrode plate and the negative electrode current collector were bonded via a negative electrode-side carbon layer. The thickness of the negative electrode-side carbon layer was set to 10 μm.

[0062] 3. Fabrication of Lithium Secondary Batteries Between the positive and negative cans that constitute the battery case, the positive electrode collector, the positive electrode carbon layer, the separator-integrated positive electrode plate, the negative electrode plate, the negative electrode carbon layer, and the negative electrode collector were stacked in this order from the positive electrode can to the negative electrode can, and after filling with electrolyte, the positive and negative cans were crimped with a gasket to seal. In this way, a coin cell type lithium secondary battery with a diameter of 12 mm and a thickness of 1.0 mm was produced. At this time, the electrolyte used was a solution in which LiBF4 was dissolved to a concentration of 1.5 mol / L in an organic solvent in which ethylene carbonate (EC) and γ-butyrolactone (GBL) were mixed in a volume ratio of 1:3.

[0063] 4. Evaluation of the middle class 4a. Composition analysis of separator-integrated positive electrode plate and measurement of intermediate layer thickness The separator-integrated positive electrode plate was polished with a cross-section polisher (CP) (JEOL Ltd., IB-15000CP), and the obtained cross section was observed with an SEM (JEOL Ltd., JSM-IT-500). Furthermore, for the obtained SEM image, point analysis was performed on the perpendicular line to the laminated surface of the separator layer / intermediate layer / positive electrode layer from the separator to the positive electrode using EDS, and the content ratio of Co and Mg was obtained. When the SEM image of the intermediate layer was analyzed by EDS, the first point where Mg / Co<1 was determined as the end of the intermediate layer on the separator side (the start point of the intermediate layer), and the first point where Mg / Co<0.01 (i.e., the point where the Mg content is less than 1% relative to the Co content) was determined as the end of the intermediate layer on the positive electrode side (the end point of the intermediate layer), and the distance between these two points was determined as the intermediate layer thickness.

[0064] 4b. Measurement of porosity of the intermediate layer of the separator-integrated positive electrode The separator-integrated positive electrode plate was polished with a cross-section polisher (CP) (JEOL Ltd., IB-15000CP), and the cross section was observed with an SEM (JEOL Ltd., JSM-IT-500). Furthermore, the part constituting the intermediate layer in the obtained SEM image was binarized using the image analysis software "Image J" so as not to damage the boundary between the sintered body part and the pore part, making the sintered body part white and the pore part black. The areas of the white and black parts in the obtained binarized image were calculated, and the value of "total area of ​​black parts / (total area of ​​white parts + total area of ​​black parts) x 100" was calculated as the porosity. The SEM image is shown in [Figure 4], and the binarized image is shown in [Figure 5].

[0065] 4c. Measurement of particle size of the intermediate layer of the separator-integrated positive electrode The separator-integrated positive electrode plate was polished with a cross-section polisher (CP) (IB-15000CP, manufactured by JEOL Ltd.), and the obtained cross section was observed with an SEM (JSM-IT-500, manufactured by JEOL Ltd.). Furthermore, for the part constituting the intermediate layer in the obtained SEM image, five perpendicular lines were arbitrarily drawn to the lamination surface, and the length along which the oxide constituting the intermediate layer was continuous on these perpendicular lines was measured. The average value of the continuous lengths thus obtained was taken as the average particle diameter.

[0066] 5. Cycle Characterization 5a. Initial battery capacity evaluation The battery capacity was confirmed using the obtained battery in an environment of 25° C. The battery was charged at a constant current of 0.2 C until the voltage reached 2.7 V. The battery was discharged at a constant current of 0.2 C until the voltage reached 1.5 V. The discharge capacity thus obtained was taken as the initial capacity.

[0067] 5b. High-speed charge / discharge cycle test Next, a high-speed charge-discharge cycle test was carried out. The charge-discharge cycle test was carried out by repeating charge and discharge 1000 times in an environment of 25°C. Charging was performed at a constant voltage of 2.7V until the current value reached 0.2C. Discharging was performed at a constant current of 1C until the voltage reached 1.5V.

[0068] 5c. Capacity retention evaluation after 1000 cycles The battery capacity was confirmed in an environment of 25°C for the battery that had been repeatedly charged and discharged 1000 times. The battery was charged at a constant current of 0.2C until the voltage reached 2.7V. The battery was discharged at a constant current of 0.2C until the voltage reached 1.5V. The discharge capacity thus obtained was taken as the capacity after 1000 cycles. This value was divided by the initial capacity and multiplied by 100 to obtain the capacity retention rate (%) after 1000 cycles.

[0069] [Example 2] A separator-integrated positive electrode, a negative electrode, and a lithium secondary battery were produced in the same manner as in Example 1, except that when producing an LCO-MgO mixed green sheet (intermediate layer green sheet), the volume-based D50 of the particles of the LCO powder mixed with the MgO powder was set to 0.5 μm, and the amount of the binder was set to 10 parts by weight, and various evaluations were performed.

[0070] [Example 3] A separator-integrated positive electrode, a negative electrode, and a lithium secondary battery were produced in the same manner as in Example 1, except that when producing an LCO-MgO mixed green sheet (intermediate layer green sheet), the volume-based D50 of the particles of the LCO powder mixed with the MgO powder was set to 4 μm, and the amount of the binder was set to 8 parts by weight, and various evaluations were performed.

[0071] [Example 4] No LCO-MgO mixed green sheet (intermediate layer green sheet) was produced, and only the positive electrode green sheet and the separator green sheet were stacked and pressed together to produce the laminate. Next, this pressed laminate was degreased at 600°C for 5 hours, and then heated to 950°C at 1000°C / h and held for 20 hours for firing, and then cooled. In this way, a separator-integrated positive electrode plate including three layers, a positive electrode layer (LCO sintered body layer), an intermediate layer, and a separator layer (MgO separator layer), was obtained. A separator-integrated positive electrode, a negative electrode, and a lithium secondary battery were produced in the same manner as in Example 1 except for these, and various evaluations were performed.

[0072] An SEM image of the separator-integrated positive electrode plate obtained in Example 4 is shown in [Figure 2]. In addition, the EDS analysis results at each point (points 4 to 7) of the intermediate layer marked in the SEM image of [Figure 2] are shown in [Figure 3]. As shown in [Figure 3], the Co content indicated by the square label increased from the separator side (point 4) to the positive electrode layer side (point 7) in the intermediate layer, and Co approached 100% in the positive electrode layer. The Mg content indicated by the diamond label monotonically decreased from the separator side to the positive electrode layer side in the intermediate layer. The Mg / Co ratio monotonically decreased from the separator side (point 4) to the positive electrode layer side (point 7) in the intermediate layer. decrease did.

[0073] [Example 5] The pressed laminate was degreased at 600°C for 5 hours, and then fired by raising the temperature to 950°C at 1000°C / h and holding the temperature for 30 minutes. In the same manner as in Example 4, except that, a separator-integrated positive electrode, a negative electrode, and a lithium secondary battery were produced and various evaluations were performed.

[0074] [Example 6] A separator-integrated positive electrode, a negative electrode, and a lithium secondary battery were produced in the same manner as in Example 1, except that when producing an LCO-MgO mixed green sheet (intermediate layer green sheet), the volume-based D50 of the particles of the LCO powder to be mixed with the MgO powder was set to 10 μm, the amount of binder was set to 30 parts by weight, and the thickness of the green sheet after firing was set to 50 μm, and various evaluations were performed.

[0075] [Example 7] The pressed laminate was degreased at 600°C for 5 hours, and then fired by raising the temperature to 950°C at 1000°C / h and holding the temperature for 5 minutes. In the same manner as in Example 4, except that, a separator-integrated positive electrode, a negative electrode, and a lithium secondary battery were produced and various evaluations were performed.

[0076] [Example 8] A separator-integrated positive electrode, a negative electrode, and a lithium secondary battery were produced in the same manner as in Example 6, except that the thickness of the LCO-MgO mixed green sheet (intermediate layer green sheet) was set to 70 μm after firing, and various evaluations were performed.

[0077] [Example 9] A separator-integrated positive electrode, a negative electrode, and a lithium secondary battery were produced in the same manner as in Example 1 except that the volume-based D50 of the LCO powder particles to be mixed with the MgO powder was 0.5 μm, the amount of the binder was 8 parts by weight, and the green sheet had a thickness of 5 μm after firing, which was used as LCO-MgO mixed green sheet 1 (intermediate layer green sheet 1), and the volume-based D50 of the LCO particles to be mixed was 7 μm, the amount of the binder was 20 parts by weight, and the green sheet had a thickness of 10 μm after firing, which was used as LCO-MgO mixed green sheet 2 (intermediate layer green sheet 2).The positive electrode green sheet, intermediate layer green sheet 1, intermediate layer green sheet 2, and separator green sheet were stacked in this order, and other similar procedures were followed to produce the separator-integrated positive electrode, negative electrode, and lithium secondary battery, and various evaluations were performed.

[0078] [Example 10] A separator-integrated positive electrode, a negative electrode, and a lithium secondary battery were produced in the same manner as in Example 1 except that the volume-based D50 of the LCO powder particles to be mixed with the MgO powder was 0.5 μm, the amount of the binder was 8 parts by weight, and the green sheet had a thickness of 5 μm after firing. This was used as LCO-MgO mixed green sheet 1 (intermediate layer green sheet 1), and a volume-based D50 of the LCO particles to be mixed was 7 μm, the amount of the binder was 20 parts by weight, and the green sheet had a thickness of 5 μm after firing. The positive electrode green sheet, intermediate layer green sheet 2, intermediate layer green sheet 1, intermediate layer green sheet 2, and separator green sheet were stacked in this order. A separator-integrated positive electrode, a negative electrode, and a lithium secondary battery were produced and various evaluations were performed.

[0079] [Comparative Example 1] A separator-integrated positive electrode, a negative electrode, and a lithium secondary battery were produced in the same manner as in Example 4, except that the pressed laminate was degreased at 600°C for 5 hours, and then fired by raising the temperature to 800°C at 1000°C / h and holding the temperature for 10 minutes. In addition, the SEM images were analyzed by EDX to confirm that no intermediate composed of a mixed oxide layer containing Co and Mg was present, and cycle characteristics were evaluated.

[0080] The evaluation results of the lithium secondary batteries of Examples 1 to 10 and Comparative Example 1 are shown in [Table 1].

[0081] [Table 1]

[0082] As shown in Table 1, in Examples 1 to 10 having an intermediate layer between the positive electrode and the separator, the capacity retention rate after 1000 cycles was 79% to 95%. In other words, a lithium secondary battery with excellent durability was obtained in which the discharge capacity was maintained even when charging and discharging was repeated many times. On the other hand, in Comparative Example 1 having no intermediate layer, the capacity retention rate after 1000 cycles was 71%, which was not as good as the Examples. Furthermore, in the lithium secondary batteries having an intermediate layer with a thickness of 1 μm or more and 50 μm or less (Examples 1 to 5, 9, and 10), the capacity retention rate after 1000 cycles was 84% ​​to 95%, and the cycle characteristics were better.

[0083] Furthermore, among Examples 1 to 10, Examples 1 and 2, in which the porosity of the intermediate layer is 15% or more and 50% or less, enable the electrolyte to be easily filled into the pores without leaving any gaps, and as a result, the intermediate layer does not significantly impede the movement of Li between the positive and negative electrodes during charging and discharging, enabling faster charging and discharging. Furthermore, among Examples 1 to 10, Examples 1, 3, 4, 9, and 10 in which the average particle size of the intermediate layer was 1 μm or more and 10 μm or less all had a capacity retention rate of 90% or more after 1000 cycles, and showed particularly excellent cycle characteristics. Furthermore, Example 4, in which the ratio of the amount of Mg present in the intermediate layer decreases from the side in contact with the separator to the side in contact with the positive electrode, exhibited particularly excellent cycle characteristics, with a capacity retention rate of 94% after 1,000 cycles. Furthermore, Example 9, in which two intermediate layers with different porosities were formed, and Example 10, in which three intermediate layers were formed, showed particularly excellent cycle characteristics, with capacity retention rates after 1,000 cycles of 95% and 94%, respectively.

[0084] It should be understood that the embodiments disclosed herein are illustrative in all respects and are not limiting in any respect. The scope of the present disclosure is defined by the claims, not the above description, and is intended to include all modifications within the meaning and scope of the claims. [Explanation of symbols]

[0085] 10 lithium secondary battery, 12 positive electrode layer, 13 positive electrode carbon layer, 14 positive electrode current collector, 15 intermediate layer, 16 negative electrode layer, 17 negative electrode carbon layer, 18 negative electrode current collector, 20 separator, 22 electrolyte, 24 exterior body, 24a positive electrode can, 24b negative electrode can, 24c gasket.

Claims

1. a positive electrode made of a sintered body containing lithium cobalt oxide; A negative electrode; a separator interposed between the positive electrode and the negative electrode and made of a sintered body containing magnesia; Equipped with An intermediate layer composed of an oxide containing Co and Mg is further provided between the positive electrode and the separator. Lithium secondary battery.

2. the separator is a plate-like separator including a first main surface and a second main surface located on the opposite side to the first main surface in a thickness direction, The positive electrode, the intermediate layer, and the separator are an integrally formed sintered plate. The lithium secondary battery according to claim 1 .

3. 3. The lithium secondary battery according to claim 1, wherein the intermediate layer has a thickness of 1 μm or more and 50 μm or less.

4. 4. The lithium secondary battery according to claim 1, wherein the intermediate layer has a porosity of 15% or more and 50% or less.

5. 5. The lithium secondary battery according to claim 1, wherein an average particle size of the oxide constituting the intermediate layer is 1 μm or more and 10 μm or less, when an average value of a length over which the oxide is continuously present is defined as the average particle size.

6. 6. The lithium secondary battery according to claim 1, wherein a ratio (Mg / Co) of the amounts of Mg and Co present in the intermediate layer decreases from a side in contact with the separator toward a side in contact with the positive electrode.

7. 7. The lithium secondary battery according to claim 1, wherein the intermediate layer has a first portion and a second portion, and the porosity of the first portion and the porosity of the second portion are different from each other.

Citation Information

Patent Citations

  • Non-aqueous electrolyte rechargeable battery

    JP2004207253A

  • All-solid lithium ion secondary battery and method of manufacturing the same

    JP2016225281A

  • Lithium secondary battery

    JP6643528B1

  • Lithium battery and method for manufacturing the same

    WO2009063747A1

  • Lithium secondary battery

    WO2019221144A1